Data Security and Privacy on Blockchain Technology - Willson Mangoki (International Journal of Information Technology and Business, 2023)
Healthcare is an aspect that possibly to use of blockchain technology, for example for historical treatment, health insurance and patient medical records. In health services, personal health data will be recorded in the form of a blockchain. This research explains its mechanism and implementation in the healthcare field. On the other hand, this study also discussed the vulnerability caused by the mechanism that applies in the blockchain.